2013
DOI: 10.1371/journal.pone.0081540
|View full text |Cite|
|
Sign up to set email alerts
|

The Autophagy-Related Marker LC3 Can Predict Prognosis in Human Hepatocellular Carcinoma

Abstract: BackgroundDefects of autophagy and endoplasmic reticulum (ER) stress are related to many diseases and tumors. However, only a few studies have examined hepatocellular carcinoma (HCC) as related to these processes. Therefore, in this study, we investigated the expression and extent of autophagy and ER stress-related markers in HCC and their influence on clinical characteristics and prognosis for each protein.MethodologyThe expression of autophagy-related markers (LC3 and Beclin-1) and ER stress-related markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 39 publications
6
60
0
Order By: Relevance
“…We further observed that the inhibition of SCD1 resulted in cell death accompanied by a marked increase According to current reports, autophagy is a dual regulator in cancer initiation and development [49; 50; 51], including in HCC [18; 19; 20; 21]. In this study, we found that LC3 protein expression was significantly decreased in HCC and that positive LC3 expression was correlated with good clinical results in HCC patients, which is consistent with findings recently reported by another group [23]. Moreover, the results reported by Mathew et al [52] provide evidence to demonstrate that autophagy-defective tumor cells exhibit P62 accumulation, which promotes tumorigenesis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We further observed that the inhibition of SCD1 resulted in cell death accompanied by a marked increase According to current reports, autophagy is a dual regulator in cancer initiation and development [49; 50; 51], including in HCC [18; 19; 20; 21]. In this study, we found that LC3 protein expression was significantly decreased in HCC and that positive LC3 expression was correlated with good clinical results in HCC patients, which is consistent with findings recently reported by another group [23]. Moreover, the results reported by Mathew et al [52] provide evidence to demonstrate that autophagy-defective tumor cells exhibit P62 accumulation, which promotes tumorigenesis.…”
Section: Discussionsupporting
confidence: 92%
“…A scoring system was applied as previously described [23]. In brief, a staining index for each case was determined by multiplying the score for the intensity of cytoplasmic staining (none staining = 0, weak = 1, moderate =2, strong = 3) with the score for the proportion of stained tumor cytoplasm (none = 0, <10% = 1, 10-50% = 2, >50% = 3).…”
Section: Immunohistochemistry and Evaluation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…This suppression is attributed to low levels in grade 2 compared to grade 1 HCC. Higher grade is associated with hepatocyte dedifferentiation and a worse prognosis [43,44]. Further research has to evaluate a potential prognostic value of AnxA6 in liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[28] and associated with longer OS in advanced stage of HCC. [29] In addition, LC3 is an independent predictor of HCC recurrence after surgery only in the context of large tumors. [28] These data support aberrant autophagy activates tumorigenesis.…”
Section: Atg In Hccmentioning
confidence: 99%